[OP.LB.02.09] WHAT ANGIOTENSIN CONVERTING ENZYME GENOTYPE AND HIGH BLOOD PRESSURE HAVE IN COMMON IN PORTUGUESE CENTENARIANS?. (September 2016) - Pereira Da Silva, A.; Ramos Marques, N.; Matos, A.; Gil, A.; Gorjão Clara, J.; Bicho, M.
Abstract : Objective: To assess, in a sample of Portuguese Centenarians compared with a control sample of lower age individuals, the blood pressure levels, the distribution of genotypes associated with the renin-angiotensin-aldosterone axis and its association with hypertension. Design and method: The study comprised 253 centenarians, with a mean age of 100.3 ± 2.0 years old, from different regions of Portugal. The control group included 268 individuals with mean age of 67.52 ± 3.27, both genders. Hypertension was defined using either ESH/ESC 2013 criteria or the fact of being under chronic anti-hypertensive medication. Controlled blood pressure values were considered according to JNC8. For the blood pressure measurements a Colson MAM BP3AA1-2 device was used. Genotyping of Angiotensin Converting Enzyme (ACE) (rs4646994), Angiotensinogen (AGT) (rs699; rs4762) and Angiotensin II receptor 1 (AGTR1) (rs5182) were performed through a high-throughput DNA Microchip platform using iPlex MassArray system from Sequenom. PCR Malditof mass spectrometry. Results: According to hypertensive criteria, 62.8% (N = 159) of the centenarian's individuals were hypertensive and 79.5% (N = 213) of control group were hypertensive. We found that, to be normotensive is a protective factor in achieving longevity (OR = 0.252 CI 95% = 0.138–0.461, p < 0.00001). Furthermore the ACE-genotypes, adjusted to the level of blood pressure, II genotype (OR = 7.510 CI95% = 3.397–16.605, p < 0.00001), and ID genotype (OR = 2.072 CI 95% = 1.223–3.508, p = 0.007) versus DD genotype (referent), were risk factors against longevity. The same was verified for normotensive and controlled centenarians (Genotype II: OR = 8.263 CI95% = 3.7–18.453, p < 0.00001; Genotype ID: OR = 2.146 CI95% = 1.262–3.648, p = 0.005). There were no significant differences in the distribution of frequencies of the other studied genotypes. Conclusions: The ACE polymorphism is associated with longevity in the context of Portuguese centenarians. The blood pressure as well as ACE-genotypes may be independent risk factors for longevity. Hypertension exists within the centenarians, but mostly, it is controlled and of mild degree, with no apparent differences between genders. So, it is not only hypertension that prevents us from reaching 100 years, but other factors, e.g., ACE gene variation, due to its pleiotropic effects, being DD-genotype, a possible candidate in the journey of greater longevity.